Taiwan Automated Telescope Network - Dean-Yi Chou; Ming-Tsung Sun; Javier Fernandez Fernandez; Li-Han Wang; Antonio Jimenez; Alexander Serebryanskiy; Shuhrat Ehgamberdiev (Advances in Astronomy)
A global network of small automated telescopes, the Taiwan Automated Telescope (TAT) network, dedicated to photometric measurements of stellar pulsations, is under construction. Two telescopes have been installed in Teide Observatory, Tenerife, Spain and Maidanak Observatory, Uzbekistan. The third telescope will be installed at Mauna Loa Observatory, Hawaii, USA. Each system uses a 9-cm Maksutov-type telescope. The effective focal length is 225 cm, corresponding to an f-ratio of 25. The field of view is 0.62 degree square. The images are taken with a 16-bit 1024×1024 CCD camera. The telescope is equipped with UBVRI filters. Each telescope is fully automated. The telescope can be operated either interactively or fully automatically. In the interactive mode, it can be controlled through the Internet. In the fully automatic mode, the telescope operates with preset parameters without any human care, including taking dark frames and flat frames. The network can also be used for studies that require continuous observations for selected objects.